Polymethylaluminoxane organic frameworks (sMAOF) – highly active supports for slurry phase ethylene polymerisation. Issue 16 (14th July 2021) - Kilpatrick, Alexander F. R.; Geddes, Harry S.; Turner, Zoë R.; Buffet, Jean-Charles; Goodwin, Andrew L.; O'Hare, Dermot
Abstract : A series of modified solid polymethylaluminoxane (sMAO) catalyst supports have been developed for slurry phase ethylene polymerisation, using aryl di-ol modifier groups. Abstract : A series of modified solid polymethylaluminoxane (sMAO) catalyst supports have been developed for slurry phase ethylene polymerisation, using aryl di-ol modifier groups. Characterisation using ICP-MS analysis, X-ray total scattering, SEM–EDX, diffuse FT-IR and solid state NMR spectroscopy shows that the organic linker groups are uniformly distributed in a proposed organic framework stucture we call a "sMAOF". When used as a support for rac -ethylenebis(1-indenyl) zirconium dichloride, (EBI)ZrCl2, these linker modified sMAOF materials provide a 40% enhancement in polymerisation activity with respect to unmodified sMAO: activities of 163 × 10 3 and 116 × 10 3 kgPE molZr −1 h −1 at 80 °C for (EBI)ZrCl2 supported on sMAOF(1, 4-HO(C6 F4 )OH) and sMAO, respectively. The observed activity increase is correlated with the higher BET surface area and increased porosity in the linker modified sMAOF activating support.